2021
DOI: 10.1103/physrevfluids.6.034602
|View full text |Cite
|
Sign up to set email alerts
|

Scaling of turbulence intensities up to Reτ=106 with a resolvent-based quasilinear approximation

Abstract: A minimal form of quasi-linear approximation (QLA), recently proposed with a stochastic forcing and POD modes (Hwang & Ekchardt, J. Fluid Mech., 2020, 894:A23), has been extended by employing a resolvent framework. A particular effort is made to reach an extremely high Reynolds number by carefully controlling the approximation without loss of the general scaling properties in the spectra, while setting out the main limitations and accuracy of the proposed QLA with possibility of further improvement. The QLA is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 77 publications
(228 reference statements)
3
21
0
Order By: Relevance
“…In this respect, the QL model can further be improved from various perspectives: for example, in the context of the present QL/GQL models, λ x,c can further be considered as a function of λ z , or, alternatively, one can introduce energetically neutral stochastic forcing to enrich the dynamics. Indeed, the latter idea was central to the recent work by Hwang & Eckhardt (2020) and Skouloudis & Hwang (2021), where a minimal QL approximation, much simpler than the QL/GQL models in the present study, was shown to reproduce the key statistical behaviours, if the mean-fluctuation dynamics is captured with a suitable model for the self-interacting nonlinear term. In the context of the present QL/GQL models, λ x,c can further be considered as a function of λ z .…”
Section: Multi-scale Dynamics In the Ql And Gql Modelsmentioning
confidence: 81%
See 1 more Smart Citation
“…In this respect, the QL model can further be improved from various perspectives: for example, in the context of the present QL/GQL models, λ x,c can further be considered as a function of λ z , or, alternatively, one can introduce energetically neutral stochastic forcing to enrich the dynamics. Indeed, the latter idea was central to the recent work by Hwang & Eckhardt (2020) and Skouloudis & Hwang (2021), where a minimal QL approximation, much simpler than the QL/GQL models in the present study, was shown to reproduce the key statistical behaviours, if the mean-fluctuation dynamics is captured with a suitable model for the self-interacting nonlinear term. In the context of the present QL/GQL models, λ x,c can further be considered as a function of λ z .…”
Section: Multi-scale Dynamics In the Ql And Gql Modelsmentioning
confidence: 81%
“…stochastic forcing, eddy viscosity, etc. ): for example, stochastic structural stability theory (Farrell & Ioannou 2003, 2007, 2012, direct statistical simulation (Marston, Conover & Tobias 2008;Tobias & Marston 2013), self-consistent approximation for linearly unstable flows (Mantič-Lugo, Arratia & Gallaire 2014;Mantič-Lugo & Gallaire 2016), minimal QL approximation augmented with an eddy-viscosity model (Hwang & Eckhardt 2020;Skouloudis & Hwang 2021), restricted nonlinear model (RNL) (Thomas et al 2014(Thomas et al , 2015Farrell, Gayme & Ioannou 2017;Pausch et al 2019;Hernández & Hwang 2020) and generalised quasilinear (GQL) approximations (Bakas & Ioannou 2013, 2014Bakas, Constantinou & Ioannou 2015;Constantinou 2015;Marston, Chini & Tobias 2016;Tobias & Marston 2017) in the context of atmospheric turbulence.…”
Section: Introductionmentioning
confidence: 99%
“…2013; Hwang 2016; Hwang, Willis & Cossu 2016; McKeon 2017; Eckhardt & Zammert 2018; Doohan, Willis & Hwang 2019; McKeon 2019; Vadarevu et al. 2019; Yang, Willis & Hwang 2019; Hwang & Eckhardt 2020; Hwang & Lee 2020; Skouloudis & Hwang 2021).…”
Section: Introductionmentioning
confidence: 99%
“…As discussed in the cited paper, even with restricted wavenumbers and frequencies, such a superposition is non-unique, as there are several combinations of forcing modes that lead to the same overall Reynolds shear stress. While the approach of Skouloudis & Hwang (2021) leads to correct Reynolds number trends, a quantitative comparison with simulation data reveals differences. Information on nonlinear terms driving flow responses may be built into dynamic attached-eddy models for more accurate predictions.…”
Section: Introductionmentioning
confidence: 97%
“…A related effort is the work of Skouloudis & Hwang (2021), who superpose resolvent modes with various wavenumbers, as a representation of attached eddies, so as to recover the Reynolds shear stress of channels. This is referred to as a quasi-linear approximation (QLA), which may be seen as a dynamic model of attached eddies based on the linearised Navier-Stokes operator.…”
Section: Introductionmentioning
confidence: 99%